2004
DOI: 10.1038/sj.mp.4001609
|View full text |Cite
|
Sign up to set email alerts
|

Associations between prepulse inhibition and executive visual attention in children with the 22q11 deletion syndrome

Abstract: The 22q11 deletion syndrome (DS) results in the loss of approximately 30 gene copies and is associated with possible physical anomalies, varied learning disabilities, and a specific cluster of neurocognitive deficits, including primary impairment in working memory, executive visual attention, and sensorimotor processing. Retrospective studies have suggested that children with 22q11DS are at 25 times greater risk of developing schizophrenia, thus specification of early brain network vulnerabilities among childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 51 publications
1
44
1
Order By: Relevance
“…We (e.g. Bish et al, 2005) and others (notably Sobin et al, 2004, Sobin, Kiley-Brabeck, & Karayiorgou, 2005) have begun to decompose the different kinds of attentional dysfunctions experienced by children with DS22q11.2 and to make inferences about the different neural basis of each one and its possible contribution to other outcomes including the risk for psychosis later in life.…”
Section: Discussionmentioning
confidence: 99%
“…We (e.g. Bish et al, 2005) and others (notably Sobin et al, 2004, Sobin, Kiley-Brabeck, & Karayiorgou, 2005) have begun to decompose the different kinds of attentional dysfunctions experienced by children with DS22q11.2 and to make inferences about the different neural basis of each one and its possible contribution to other outcomes including the risk for psychosis later in life.…”
Section: Discussionmentioning
confidence: 99%
“…It can be modulated by both attention and emotion. Several lines of evidence suggest that this early-stage gating is modulated by higher order cognitive processes (Braff et al 2001;Swerdlow et al 2001;Sobin et al 2005;Bjornsson et al 2006). A prepulse presented at short lead intervals reduces the perceived loudness of the probe stimulus, suggesting prepulse-mediated inhibition of auditory cortex processing (Perlstein et al 1993).…”
Section: Aces Relieves Tinnitus Through Improving Central Auditory Prmentioning
confidence: 99%
“…A study in humans further suggested that the SCZ risk allele (C) of rs9960767 in this gene was significantly associated with reduced PPI in both healthy controls and patients with SCZ spectrum disorder (Quednow et al, 2011). Reduced PPI is an important intermediate phenotype of SCZ and is believed to be modulated by attention as assessed by the continuous performance test (CPT) (Hazlett et al, 2001(Hazlett et al, , 2008, the attention network test (ANT) (Sobin et al, 2005) and the Stroop test (Molina et al, 2009). However, the role of the TCF4 gene in the etiology of attention function has not been studied.…”
Section: Introductionmentioning
confidence: 99%